2018
DOI: 10.3389/fncel.2018.00130
|View full text |Cite|
|
Sign up to set email alerts
|

Cell Mechanotransduction With Piconewton Forces Applied by Optical Tweezers

Abstract: Mechanical stresses are always present in the cellular environment and mechanotransduction occurs in all cells. Although many experimental approaches have been developed to investigate mechanotransduction, the physical properties of the mechanical stimulus have yet to be accurately characterized. Here, we propose a mechanical stimulation method employing an oscillatory optical trap to apply piconewton forces perpendicularly to the cell membrane, for short instants. We show that this stimulation produces membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 36 publications
0
47
0
1
Order By: Relevance
“…The proposed NOTOD is not only compact, having high optical efficiency, but also a flexible tool for optical method to control trapped bead in space and to stretch different kind of DNA molecules. Using organic dye with high nonlinearity, the optical trap efficiency of NOTOD is high enough, which can trap nanoparticle [21,22] and stretch DNA molecule [44][45][46][47], instead of using ultrafast pulsed laser.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed NOTOD is not only compact, having high optical efficiency, but also a flexible tool for optical method to control trapped bead in space and to stretch different kind of DNA molecules. Using organic dye with high nonlinearity, the optical trap efficiency of NOTOD is high enough, which can trap nanoparticle [21,22] and stretch DNA molecule [44][45][46][47], instead of using ultrafast pulsed laser.…”
Section: Discussionmentioning
confidence: 99%
“…Different configurations have been developed to perform nanoindentation with optical tweezers on cells. Indentation can be performed axially by moving the sample through a piezoelectric stage against a trapped dielectric microsphere (Coceano et al 2016;Yousafzai et al 2016), or by moving the trap towards the cell either in a linear (Dy and Sugiura 2013) or in an oscillatory way (Falleroni et al 2018). Another possibility is to use a lateral indentation approach, where the sample or the trap is moved along the image plane against a perpendicular cell membrane (Zhou et al 2014).…”
Section: Nanoindentationmentioning
confidence: 99%
“…It has been recently demonstrated that cellular calcium transients can be precisely induced in mouse neuroblastoma NG108-15 cells with a periodic mechanical stimulation method employing an oscillatory optical trap to apply gentle forces perpendicularly to the cell membrane (Falleroni et al 2018). The induced calcium transients depended on the stimulus strength: the mechanical forces exerted in experiments had maximum values in the range 10-18 pN and induced detectable changes of intracellular Ca 2+ ; a decrease in the trap stiffness by a factor of 2, led to maximum forces in the range 4-10 pN, and no calcium activation was observed (Falleroni et al 2018). Besides force-triggered signals, optical tweezers can be used to trigger specific signals with high spatio-temporal resolution by positioning ligand-coated beads on the cell membrane.…”
Section: Measuring Mechanotransduction Signals In Living Cellsmentioning
confidence: 99%
“…This is achieved by tethering polystyrene beads to cell membranes, which can be manipulated when subjected to focused light. Using this technique, a recent study highlighted how mouse neuroblastoma cells respond to forces ranging from 5 to 20 pN by activation of Ca 2+ ion channels at defined force thresholds (Falleroni et al, 2018). Optical tweezers have been largely applied and optimized to 2D single cell scenarios and thus may prove less attractive to mechanically stimulate more complex 3D multicellular tissues and organoids.…”
Section: Extrinsic Control Of Cellular Forces Through Motorized Devicmentioning
confidence: 99%